Discussion of Decision Theory Aspects of Internal Control System Design/ Compliance and Substantive Tests - Taylor, Robert G. (Journal of Accounting Research, 1975)
In general, I believe William Kinney's paper makes a very worthwhile contribution in that it forces us to do some concrete thinking about the relationship in auditing of compliance tests (CT's), tests of details (TD's), and analytical review (AR). The decision theory approach used in the paper is a very logical and possibly a very concise way of discussing optimum strategy with respect to the correct mix of these three audit procedures. For the nonmathematically oriented reader, however, the paper is very difficult to follow, and I think that even the mathematically oriented reader might find the paper difficult to follow at times. For example, an earlier paper by Kinney on the same subject is referred to and integrated without sufficient supportive explanation. Numbers appear which I found impossible to find in the related tables. In addition, I believe that the overall concept underlying the paper needs to be refined and that some translation for the layman is necessary if the intelligent auditor is to understand the underlying concept and to implement it successfully. A basic flaw of the paper relates to the fact that the model described by Kinney is greatly oversimplified and needs to be expanded if it is to be operationally useful to the practicing auditor. Part of the reason for the oversimplified model is not Kinney's fault. The Statement on Auditing Standards No. 1, section 320, does not differentiate accounts, and as a result, Kinney naturally uses a single account in his model. This over-simplification is unfortunate since the four major accounts encountered by auditors-Assets, Liabilities, Revenues, and Expenses-are very much different. For example, it is not permissible to avoid tests of details of certain